2019
DOI: 10.12659/msm.912375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristic and Pathogen Spectrum of Neonatal Sepsis in Guangzhou City from June 2011 to June 2017

Abstract: Background Preterm and low birth weight (birth weight <2500 g) neonates are vulnerable to sepsis, and the causative pathogens vary in different regions and times. The objective of this study was to identify common organisms leading to neonatal sepsis and identify the characteristic of patients infected with different bacteria, which may help in the selection of antibiotics for empirical treatment. Material/Methods We retrospectively collected the clinical and microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
26
3
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 26 publications
11
26
3
1
Order By: Relevance
“…In some regions from developing countries, CoNS have been reported to play a less important role [22,23]. In China, Guo et al found that CoNS was the third common organism responsible for LOS in South China [24], while Li et al found that CoNS was the most common organism in Southeast China [25]. The results in our study are in line with Guo's study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In some regions from developing countries, CoNS have been reported to play a less important role [22,23]. In China, Guo et al found that CoNS was the third common organism responsible for LOS in South China [24], while Li et al found that CoNS was the most common organism in Southeast China [25]. The results in our study are in line with Guo's study.…”
Section: Discussionsupporting
confidence: 91%
“…infection were preterm low birth weight infants. The fungi infection rate in our study is similar to the results of Guo's study [24], but significantly higher than the results of 2 other studies conducted in other regions of China [13,14].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…S . marcescens remains an important pathogen in our neonatal unit and is associated with mortality and severe neurological impairment [ 32 , 33 ], a finding which has not yet been described in other LMIC settings [ 25 , 32 , 34 39 ]. A .…”
Section: Discussionmentioning
confidence: 99%
“…aureus and Enterococcus species were responsible for most HA-BSI episodes due to Gram-positive pathogens, and these remain associated with significantly lower mortality than Gram-negative and fungal BSI pathogens [ 11 ]. Pathogen spectrum varies geographically, with most centres reporting a predominance of coagulase-negative staphylococci [ 25 , 26 , 31 , 39 , 42 , 43 ]. Coagulase-negative staphylococci were defined as pathogens in this context using a strict definition, likely resulting in underestimation of their contribution to overall HA-BSI in this study.…”
Section: Discussionmentioning
confidence: 99%